Privacy virtualisation as an element of the new gender order - A. V. Shvetsova (Цифровая социология)
The article is analysed the privacy virtualisation phenomenon, which has become a trend in the digital world. Considering virtual communication practices in the context of global sociality transformations, the author shows that their impact on gender relations is progressive; the formats differ in structural and content diversity. The overview of the most important world studies in virtuality sociology is presented. They have in common is the concern of scholars about the substitution of real interpersonal relationships by virtual ones, the blurring of boundaries between these life layers with the social loneliness growth. The methodological basis is the gender approach and its private concept – the theory of changing the gender order, within which the rules and norms regulating the private sphere are conceptualized as variable, changeable and having socio-cultural conditioning. The author proposes a theoretical model of the mechanism for choosing a virtual partner, supported by the results of an online survey, analyses the features of the formation and development of virtual relations, the possibility of moving to the real plane, depending on the motivation of actors and trust in the virtual partner. Some trends in the development of virtual private practices are noted, including the development of artificial sociality, control of the digital footprint and communication with virtual agents.